Implementasi Pasal 1 Angka 19 Peraturan Walikota Pekanbaru Nomor 138 Tahun 2020 Tentang Penyelenggaraan Perparkiran Di Kota Pekanbaru - Atthoriq, Baihaqqi Daffa; Deliana, Evi; Zulhidayat, Muhammad (Peneliti.net, 2025)
The implementation of parking policy authority by the Pekanbaru City Government is regulated under Pekanbaru City Regulation Number 20 of 2020 concerning Parking Organisation. According to this regulation, the Pekanbaru City Government is responsible for managing parking, which includes planning, implementation, supervision, and control. This research aims to examine the implementation of Article 19 of the regulation, the supporting factors, and the obstacles in supervising and managing parking officers in Pekanbaru City. The research findings highlight the importance of clear parking mechanisms and the protection of parking attendants. The applicable laws mandate that employers register parking attendants for employment social security. Failure to do so results in sanctions, including written warnings, fines, and restricted access to public services. However, the implementation faces challenges such as limited resources, lack of compliance, and enforcement difficulties. The study concludes that an effective parking policy requires a balance between authority and practical implementation. The government must ensure proper planning, supervision, and control over parking management while protecting the rights of parking attendants. Strengthening regulations, improving enforcement, and increasing public awareness are essential to achieving efficient parking governance in Pekanbaru City.